Effect of predation risk on microhabitat use by goldfish. Issue 1 (2nd January 2019) - Vijayan, Sundararaj; Kotler, Burt P.; Tamar Tov-Elem, Lotan; Abramsky, Zvika
Abstract : For prey individuals, predation risk constitutes an important cost of foraging. They respond by altering their foraging behaviour in risky areas that involves a trade-off between energy intake and safety. In particular, prey can vary the amount of time they spend in safe and risky foraging patches in response to the level of perceived predation risk. Using Giving up Densities (GUDs), we examined foraging behaviour decisions of goldfish groups foraging in open and cover habitats. We specifically compared the foraging behaviour of goldfish in the two habitats in the presence and absence of a predator (little egret). In the absence of a predator, the goldfish equalised GUDs between open and cover habitats. However, in the presence of a predator, the GUDs were significantly lower in the cover microhabitat than in the open. The goldfish spent almost twice the time foraging in the open GUD trays in the absence of the predator. The number of visits and time spent per visit to the foraging patch were significantly higher in the absence of a predator. However, the goldfish group harvested food pellets at a similar rate in both risky and non-risky environments, suggesting that in risky environments they forego apprehension and instead rely on time allocation to manage risk.